The Role of Islamic Education in Shaping National Morality: A Literature Review - Dulyapit, Apit; Ulfa, Aisya Widya (Islah: Journal of Islamic Literature and History, 2024)
Islamic education plays a crucial role in shaping the moral fabric of society by instilling ethical values and religious principles. This study aims to explore how Islamic education influences national morality through a systematic review of relevant literature. It examines the historical development of Islamic education, its methodologies, and its alignment with character-building frameworks. Furthermore, the review highlights key case studies demonstrating the effectiveness of Islamic education in fostering integrity, empathy, and social responsibility. The findings suggest that an integrative approach to Islamic education can significantly enhance moral standards at both individual and societal levels. This paper concludes with recommendations for optimizing educational strategies to better contribute to the moral development of the nation. The study underscores the importance of collaboration between educators, policymakers, and religious institutions in achieving these goals.